A random control trial of contrast baths and ice baths for recovery during competition in U/20 rugby union - Higgins, T. R.; Heazlewood, I. T.; Climstein, M. (The Journal of Strength and Conditioning Research, 2011)
Players in team sports must recover in a relatively short period of time to perform at optimal levels. To enhance recovery, cryotherapy is widely used. To date, there are limited scientific data to support the use of cryotherapy for recovery. Players (n = 26) from a premier rugby club volunteered to participate in a random control trial (RCT) using contrast baths, ice baths, and no recovery. Statistical analysis, between group and within group, with repeated measures was conducted along with determination of effect sizes in 2 field tests. Pre and postfield tests including a 300-m test and a phosphate decrement test and subjective reports were conducted during the RCT. No significant difference was identified between base tests and retests in the phosphate decrement test or the 300-m tests. Effect size calculations identified a medium to large effect (d = 0.72) for 300-m tests for contrast baths against control. Trivial effects were identified for ice baths (d = 0.17) in the 300-m test against control. Effect size calculations in the phosphate decrement test showed a trivial effect (d = 0.18) contrast baths and a negative effect (d = -0.62) for ice baths. Treatment-treatment analysis identified a large effect for contrast baths (d = 0.99) in the phosphate decrement test and a medium effect for contrast baths (d = 0.53) in the 300-m test. Effect scores across contrast baths, ice baths, and passive recovery along with subjective reports indicate a trend toward contrast baths benefiting recovery in rugby. The continued use of 5-minute ice baths for recovery should be reconsidered based on this research because trends suggest a detrimental effect.